Poly (vinyl alcohol) (PVA) nanofibers embedded with silver nanoparticles for antibacterial studies-by electrospinning method - Intan Shafinaz, Abd Manaf (2012)
In this research antibacterial study has been done by using the polymer nanofibers made from polyvinyl alcohol (PVA) embedded with silver nanoparticles. The smaller size of polymer, the surface area will increase. Simple preparation steps had been done for this study. PVA was selected as the matrix because of it special properties such as is water soluble and has excellent fiber forming ability, biocompatibility, chemical resistance and biodegradability. It is one of the good stabilizing agents. An electrospinning technique was used for the fabrication of polymer nanofibers. Recently, many researches have been done in the fabrication of nanofibers by using electrospinning method. This technique has been chosen by many researchers because of it special properties which gives nanofibers with dimensions ranging from micrometer to a few nanometers.SEM and UV-visible spectroscopy analysis has been done for the characterization of morphology of nanofibers. E. Co/i has been used as gram negative while S.Aureus has been used as gram positive. In conclusion, we state that this polymer nanofibers act as a very good antimicrobial, environmental friendly and also known as "green" nanofibers. In antibacterial studies, when the fibers were heated at higher temperatures, it did not show any antibacterial activity. When it was heated at low temperature, it showed excellent antibacterial activity.